The dynamics and impact of foot and mouth disease in smallholder farming systems in South-East Asia: A case study in Laos - Perry, Brian D.; Gleeson, L.J.; Khounsey, S.; Bounma, P.; Blacksell, Stuart D. (World Organisation for Animal Health, 2002)
There is a general lack of data on the different patterns of dynamics and impact of foot and mouth disease (FMD) in South-East Asia and the impact the disease has on different sectors, in particular the smallholder sector in which livestock play such an important role. A pilot study was conducted of a recent outbreak of FMD that swept across the southern part of Laos during the second half of 1999. The main objectives of the study were to investigate the possible routes of transmission of the disease and the impact of FMD on the predominantly smallholder rice/livestock production system of Savannakhet Province. The study was performed by group interviews of farmers in ten villages, located in five districts across the width of the Province, and of district and provincial veterinary officials. Results suggested that the infection had probably been introduced from the eastern border and had spread rapidly west, along a principal trading route of pigs, cattle and buffalo. In the process, many villages adjacent to this trading route became infected and the disease spread rapidly within infected villages. The disease had a significant impact on the agricultural system, but the impact would have been much greater had the epidemic occurred during the season of paddy field preparation. Mortality was observed in young buffalo, cattle and pigs, and long periods of morbidity were observed in buffalo, often requiring extended treatment. The sale of livestock for cash was severely restricted, creating additional repercussions on that sector. It was concluded that the most appropriate approach to FMD control would be to prevent infected animals from entering the principal trading routes for pigs, cattle and buffalo. This will require the involvement of all the stakeholders of the livestock industry, including traders and veterinary authorities. A further tactic to be considered would be to protect livestock systems adjacent to these trading routes by vaccination. An economic study of the market incentives of both traders and smallholders is recommended and this approach is advocated in other parts of South-East Asia where livestock trading routes present the major risk of FMD outbreaks.